Properties of Carbon Nanotubes and Their Use in Potential Applications - Vojackova, Anna (Communications - Scientific letters of the University of Zilina, 2006)
Many laboratories in the world are doing research in the field of nanotechnology. Among lot of nanomaterials carbon nanotubes became very popular because of their unique properties which could be used in many applications. But first, lot of problems with their preparation need to be solved.